Housing and Social Transition in Japan - Hirayama, Yosuke; Ronald, Richard (Housing and Society Series, 2007)
Bringing together a number of perspectives on the Japanese housing system, Housing and Social Transition in Japan provides a comprehensive, challenging and theoretically developed account of the dynamic role of the housing system during a period of unprecedented social and economic change in one of the most enigmatic social, political, and economic systems of the modern world. While Japan demonstrates many of the characteristics of some western housing and social systems, including mass homeownership and consumption-based lifestyles, extensive economic growth and rapid urban modernization has been achieved in balance with traditional social values and the maintenance of the family system. Helpfully divided into three sections, Housing and Social Transition in Japan: explores the dynamics of the development of the housing system in post-war Japan deals with social issues related to housing in terms of social aging, family relations, gender and inequality addresses the Japanese housing system and social change in relation to comparative and theoretical frameworks. As well as providing challenges and insights for the academic community at large, this book also provides a good introduction to the study of Japan and its housing, economic, social and welfare system generally.